The ethics of influence : government in the age of behavioral science / Cass R. Sunstein. - Sunstein, Cass R. (Cambridge studies in economics, choice, and society., 2016)
In recent years, 'Nudge Units' or 'Behavioral Insights Teams' have been created in the United States, the United Kingdom, Germany, and other nations. All over the world, public officials are using the behavioral sciences to protect the environment, promote employment and economic growth, reduce poverty, and increase national security. In this book, Cass R. Sunstein, the eminent legal scholar and best-selling co-author of Nudge, breaks new ground with a deep yet highly readable investigation into the ethical issues surrounding nudges, choice architecture, and mandates, addressing such issues as welfare, autonomy, self-government, dignity, manipulation, and the constraints and responsibilities of an ethical state. Complementing the ethical discussion, The Ethics of Influence: Government in the Age of Behavioral Science contains a wealth of new data on people's attitudes towards a broad range of nudges, choice architecture, and mandates.